PERAN BAHAN ORGANIK DALAM MENURUNKAN DAMPAK PAPARAN PESTISIDA TERHADAP KESUBURAN TANAH DAN SERAPAN HARA TANAMAN SAWI - Novalia Kusumarini; S Sayifudin; Feppy Dwi Kautsar; S Syekhfani (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Pesticide exposure in the soil is indicated to affect soil fertility as well as nutrient uptake by the plant due to its active ingredient that can affect soil sorption. This research focused on organic matter effect on soil fertility (pH, organic-C, N, P, K) in the soil under several doses of pesticide exposure as well as nutrients (N, P, K) uptake by the green mustard plant. Treatments consisted of control, d and four doses of pesticide application (50%, 100%, 150%, 200% of recommendation dose), four doses of pesticide application combined with two doses of manure application (0 and 2 t ha-1). Soil pH, organic C, N, P, and K were measured before treatments and after harvest. Nutrients uptake (N, P, K) and yield of green mustard were measured at harvest.Â  Results of the study showed that the exposure of pesticide in soil reduced the yield of green mustard by 40% compared to control. Nutrients (N, P, K) uptake by plant decreased by 72%, 92%, dan 78% compared to control in soil with exposure of 0,2 ml pesticide 500 ml-1 water even though with the addition of organic matter.